Synthesis, Characterization & Evaluation of Biological Efficiency of Some Transition Metal Complexes with Schiff Base E-3-(Phenylhydrazono) indolen-2-one - Israa A. Al-H. Hamdan (Journal of Global Pharma Technology, 2019)
This work involved synthesis of Schiff base derivative from the condensation reaction of the phenylhydrazine with 1H-Indole-2, 3-dione (isatin). Metal complexes of the Schiff base ligand with Cu (II), Zn (II), Fe (III), Ni (II), and Mn (II) ions were prepared by reacting ligand with the metal salts in ethanol. The chemical structures of the ligand as well as the stereo-chemical structures and geometries of the studied metal complexes were suggested depending on the results obtained from CHN analysis, H-NMR, FT-IR spectrophotometer, Uv-vis electronic spectra, conductivity measurements, and magnetic measurements. The mole ratio of the ligand to the metal ion was 1:2 with bi-dentate bonding behaviors of the coordinating ligand with the metal ions. The Metal complexes of the Schiff base ligand that prepared show variety of bioactivity against three types of bacteria. Keywords: Isatin, Schiff Bases, Metal Complexes, Antibacterial activity, Data spectra.